Ralph Compton [large type] : straight to the noose - Compton, Ralph (A Ralph Compton novel, 2015)
Mississippi charmer Abner Mason is a professional gambler and a regular on the Delta Jack, a luxurious riverboat. But luck hasn't exactly been going Mason's way. After a disastrous loss at the tables, he owes an impossible debt to the most powerful man on the ship: mysterious, ruthless Cam Greely. And Greeley's willing to do whatever it takes to get his fortune back --even threaten Mason's life. Now Mason has a single night to raise all the funds to pay off his debt by completing whatever ominous jobs Greeley has waiting for him. He just has to make it through alive ...